A TM-Pass/TE-Stop Polarizer Based on a Surface Plasmon Resonance. (2nd August 2010) - Wakabayashi, Yuu; Yamauchi, Junji; Nakano, Hisamatsu
Abstract : A TM-pass/TE-stop polarizer consisting of a metal film sandwiched between dielectric gratings is investigated using the finite-difference time-domain method. At normal incidence with respect to the grating plane, a transmissivity of more than 94% and a reflectivity of more than 98% are obtained atλ = 1.55 μ m for the TM and TE waves, respectively. The extinction ratio is more than 17 dB over a wavelength range of 1.50 μ m to 1.75 μ m. A high extinction ratio is maintained at oblique incidence, although the wavelength range shifts towards longer wavelengths. The TM-pass/TE-stop operation is also achieved with a modified structure, in which a dielectric grating is sandwiched between metal films.